Aldosterone breakthrough does not alter central hemodynamics. (October 2017) - Beenken, Andrew; Bomback, Andrew S.
Introduction: Angiotensin-converting enzyme inhibitors and angiotensin receptor blockers are widely used in congestive heart failure and chronic kidney disease, but up to 40% of patients will experience aldosterone breakthrough, with aldosterone levels rising above pre-treatment levels after 6–12 months of renin-angiotensin-aldosterone system blockade. Aldosterone breakthrough has been associated with worsening congestive heart failure and chronic kidney disease, yet the pathophysiology remains unclear. Breakthrough has not been associated with elevated peripheral blood pressure, but no studies have assessed its effect on central blood pressure. Methods: Nineteen subjects with well-controlled peripheral blood pressure on stable doses of angiotensin-converting enzyme inhibitor/angiotensin receptor blocker had aldosterone levels checked and central blood pressure parameters measured using the SphygmoCor system. The central blood pressure parameters of subjects with or without breakthrough, defined as serum aldosterone >15 ng/dl, were compared. Results: Of the 19 subjects, six had breakthrough with a mean aldosterone level of 33.8 ng/dl, and 13 were without breakthrough with a mean level of 7.1 ng/dl. There was no significant difference between the two groups in any central blood pressure parameter. Conclusions: We found no correlation between aldosterone breakthrough and central blood pressure. The clinical impact of aldosterone breakthrough likely depends on its non-genomic, pro-fibrotic, pro-inflammatory effects rather than its regulation of extracellular volume.